Antibiotic Resistance of Escherichia coli Bacteria in Cattle: Challenges to Food Self-Sufficiency in Indonesia - Alfiana Laili Dwi Agustin; Novarina Sulsia Ista'In Ningtyas; Lita Rakhma Yustinasari; Agus Widodo; I Putu Cahyadi Putra (Mandalika Veterinary Journal, 2026)
Antimicrobial resistance (AMR) in the livestock sector, particularly in cattle farming in Indonesia, requires special attention as it is a rather concerning public health issue. The irrational use of antibiotics for therapy, prophylaxis, or as growth promoters has contributed to the increasing presence of resistant bacteria in beef and dairy cattle. The main challenges in controlling AMR include the lack of regulation on antibiotic use in the field, limited diagnostic facilities, low farmer awareness, and suboptimal national surveillance programs. This review synthesizes findings on the incidence of antibiotic resistance in Escherichia coli (E. coli) bacteria isolated from cattle in Indonesia. Various studies have shown that E. coli isolates from cattle in Indonesia have exhibited resistance to important antibiotics, including tetracycline, penicillin, and several β-lactam antibiotics. The presence of these resistant bacteria not only affects the effectiveness of veterinary treatments but also has the potential to transfer to humans through the food chain, direct contact, and environmental contamination. Based on these findings, control efforts need to be conducted in an integrated manner through a One Health approach, including improving farm biosecurity, strengthening antibiotic use policies, educating farmers, and developing a consistent, nationally standardized AMR surveillance program. The surveillance results from research data on E. coli bacterial resistance in Indonesia can be used to significantly reduce the risk of the spread of antibiotic resistance from the cattle sector to humans.